A Comprehensive Study of the Association between LEPR Gene rs1137101 Variant and Risk of Digestive System Cancers - HU, Wei Qiong; ZHOU, Wei Guang; ZHOU, Guang Wei; LIAO, Jia Xi; SHI, Jia Xing; XIE, FengYang; LI, Shou Heng; WANG, Yong; FENG, Xian Hong; GU, Xiu Li; CHEN, Bi Feng (Biomedical and environmental sciences, 2024)
The leptin receptor, encoded by the LEPR gene, is involved in tumorigenesis. A potential functional variant of LEPR, rs1137101 (Gln223Arg), has been extensively investigated for its contribution to the risk of digestive system (DS) cancers, but results remain conflicting rather than conclusive. Here, we performed a case–control study and subsequent meta-analysis to examine the association between rs1137101 and DS cancer risk. A total of 1,727 patients with cancer (gastric/liver/colorectal: 460/480/787) and 800 healthy controls were recruited. Genotyping of rs1137101 was conducted using a polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP) assay and confirmed using Sanger sequencing. Twenty-four eligible studies were included in the meta-analysis. After Bonferroni correction, the case–control study revealed that rs1137101 was significantly associated with the risk of liver cancer in the Hubei Chinese population. The meta-analysis suggested that rs1137101 is significantly associated with the risk of overall DS, gastric, and liver cancer in the Chinese population. The LEPR rs1137101 variant may be a genetic biomarker for susceptibility to DS cancers (especially liver and gastric cancer) in the Chinese population.